Experimental Retrieval of Target Structure Information from Laser-Induced Rescattered Photoelectron Momentum Distributions - Okunishi, M.; Morishita, T.; Prümper, G.; Shimada, K.; Lin, C. D.; Watanabe, S.; Ueda, K. (My University, 2008)
We have measured two-dimensional photoelectron momentum spectra of Ne, Ar, and Xe generated by 800-nm, 100-fs laser pulses and succeeded in identifying the spectral ridge region (back-rescattered ridges) which marks the location of the returning electrons that have been backscattered at their maximum kinetic energies. We demonstrate that the structural information, in particular the differential elastic scattering cross sections of the target ion by free electrons, can be accurately extracted from the intensity distributions of photoelectrons on the ridges, thus effecting a first step toward laser-induced self-imaging of the target, with unprecedented spatial and temporal resolutions.